The Role of Innovation in Fostering Competitiveness and Economic Growth: Evidence from Developing Economies - Terzić, Lejla (Comparative Economic Research. Central and Eastern Europe, 2017)
This paper deals with the essential features determining the role of innovation in developing economies by examining the structure of innovation measures. The economic growth and competitiveness of developing economies are powerfully connected to its innovation status. The purpose of this paper is to examine the significance of innovation in driving economic growth per capita and competitiveness in selected developing economies. In order to determine the interconnection among the variables of innovation, competitiveness, and growth, assorted methodological measurement instruments have been applied. The data were collected from both primary and secondary sources. The results suggest the importance of specific innovation dimensions for prospective economic growth in developing economies. The identical measures responsible for fragile innovation are associated to the low composite measures of innovation accomplishment. This demonstrates the enormous disparity concentrated in every innovation aspect over time, specifically in innovation output and enterprise performances between the developing economies and the EU–28 average measures. The research results indicate the usage of appropriate economic instruments in diminishing the problems that developing economies are currently dealing with.